2009
DOI: 10.1007/s00038-009-0060-8
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for estimating excess mortality due to heat waves, as applied to the 2006 California heat wave

Abstract: California experienced excess heat-wave related mortality not restricted to high heat regions. As climate change is anticipated to increase heat events, public health efforts to monitor effects assume greater importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 6 publications
3
36
0
2
Order By: Relevance
“…Citywide there were over 4% more deaths on days with a Heat Index equal to or above 100 1F compared to all other warm season days from 1997 to 2006. This finding is consistent with other studies that have found excess mortality during high heat days (Hoshiko et al, 2010; Metzger et al, 2010; New York City Department of Health and Mental Hygiene (NYCDOHMH), 2006; Semenza et al, 1996). …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Citywide there were over 4% more deaths on days with a Heat Index equal to or above 100 1F compared to all other warm season days from 1997 to 2006. This finding is consistent with other studies that have found excess mortality during high heat days (Hoshiko et al, 2010; Metzger et al, 2010; New York City Department of Health and Mental Hygiene (NYCDOHMH), 2006; Semenza et al, 1996). …”
Section: Resultssupporting
confidence: 92%
“…Excessive exposure to high heat is associated with increased rates of heat stress, heat stroke, and premature death (O'Neill and Ebi, 2009). Heat-associated mortality typically presents as excess mortality due to cardiovascular or respiratory causes during hot weather (Hoshiko et al, 2010). As a result of extreme events such as the premature deaths of 14,800 people in France during the August 2003 heat wave (Observatoire régional de santé (ORS), 2003), awareness of heat-related mortality has increased.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a large number of heat-related deaths have been reported in the United States (Center for Disease Control and Prevention 1994;Curriero et al 2002;Hoshiko et al 2010), Europe (Keatinge et al 2000a;Keatinge et al 2000b;Huynen et al 2001), and Asia (Qian et al 2008;Chung et al 2009). A recent study by Berko et al examined deaths attributed to extreme weather events from 2006 to 2010 in the United States and found that each year about 2,000 U.S. residents died from weather-related causes, and among those 31% died due to exposure to excessive heat, heat stroke, and/or sun stroke (Berko et al 2014).…”
Section: Extreme Heat and Health Impactsmentioning
confidence: 99%
“…Such extreme heat can harm human health and increase risk of heat stroke (Bouchama and Knochel 2002) and more common health problems such as respiratory and cardiovascular hospitalizations and deaths (Anderson et al 2013; Hoshiko et al 2010; Jones et al 1982; Naughton et al 2002; Weisskopf et al 2002). Heat-related health impacts can be especially severe for certain groups including those living in urban areas (Fischer et.…”
Section: Introductionmentioning
confidence: 99%